2022
DOI: 10.3390/toxins14070440
|View full text |Cite
|
Sign up to set email alerts
|

Patulin Detoxification by Recombinant Manganese Peroxidase from Moniliophthora roreri Expressed by Pichia pastoris

Abstract: The fungal secondary metabolite patulin is a mycotoxin widespread in foods and beverages which poses a serious threat to human health. However, no enzyme was known to be able to degrade this mycotoxin. For the first time, we discovered that a manganese peroxidase (MrMnP) from Moniliophthora roreri can efficiently degrade patulin. The MrMnP gene was cloned into pPICZα(A) and then the recombinant plasmid was transformed into Pichia pastoris X-33. The recombinant strain produced extracellular manganese peroxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In this study, the Mr MnP, expressed in P . pastoris as before [ 29 ], was purified using hydrophobic-interaction chromatography (Fig. 1 a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the Mr MnP, expressed in P . pastoris as before [ 29 ], was purified using hydrophobic-interaction chromatography (Fig. 1 a).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies of MnPs focus on their ability to biodegrade organic pollutants, toxins, etc. This study explored its ability in LCB decomposition by using an MnP from Moniliophthora roreri , Mr MnP, distinguished from other enzyme counterparts by its high-level secretory expression with a strong potential application prospect [ 28 , 29 ]. The effects of buffer components, pH, and H 2 O 2 on Mr MnP activity were first examined.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it entails the elicitation of systemic resistance within host plant organisms [ 36 ]. In addition, numerous studies have demonstrated that some yeast strains possess detoxification functions, converting toxins produced by fungi into non-toxic or low-toxic substances to defend against fungal attack [ 37 ]. Various attempts have been made to improve the effectiveness of antagonistic yeasts against harmful microorganisms by increasing their viability or by combining them with other physical or chemical means.…”
Section: Biocontrol Of Yeasts In Agricultural Productsmentioning
confidence: 99%
“…The prevention of PAT contamination is mainly based on controlling P. expansum through the reduction of conidial germination, germ tube elongation and inhibition of fungal growth, with a consequent decrease of PAT biosynthesis and accumulation ( Yu et al, 2020 ). Conversely, PAT degradation consists of enzymatic degradation operated by several bacterial and yeast species leading to the formation of the end-products desoxypatulinic acid, (Z)-ascladiol, and hydroascladiol ( Castoria et al, 2011 ; Ianiri et al, 2013 ; Mahunu, 2017 ; Tannous et al, 2017 ; Wei et al, 2020 ; Awuchi et al, 2021 ; Wang et al, 2022 ). Other studies show that some yeast species are also able to decrease PAT concentration through its adsorption to the cell wall ( Caridi, 2007 ; McCormick, 2013 ; Nešić et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%